Фестивальне життя Луцька на зламі тисячоліть: як це відбувалося - Лапчук, Олеся; Lapchuk, Olesya (My University, 2015)
У статті висвітлено особливості становлення та розвитку фестивального життя Луцька 80–90-х рр. ХХ ст. Проаналізовано суспільні передумови створення й розвитку (або занепаду) фестивалів міста. Розглянуто тематику та соціокультурні завдання фестивалів зазначеного періоду.Peculiarities of establishment and development of Lutsk festival life in 80-90’s of 20th century, which is already history for a new generation, is elucidated in the article. It is paid attention to the most visible of its stages, analyzed the main tendencies and possible ways of a further step of artistic efforts for cultural event organizers. It is analyzed the influence of community prerequisites for realizing festivals in the city. It is presented in details history of establishment such festivals as «Lesyna pisnia», a festival of stage plays by Lesya Ukrainka, «Rok-Kultura», «Oberig», «Beregynya», «Blagovist Volyni», «Rizdviana misteria», «Poliske lito z folklorom», «Sholom, Ukraino!». It is analyzed a theme and sociocultural tasks of festivals of the mentioned period.
Lutsk Festival Life at the turn of Millennium: how it was
Keywords: фестивалі; Луцьк; «Оберіг»; «Берегиня»; «Поліське літо з фольклором»; «Різдвяна містерія»; festivals; Lutsk; «Oberig»; «Beregynya»; «Poliske lito z folklorom»; «Rizdviana misteria»